Characterization of Particulate Matter Generated at a Nickel Smelter Using Quantitative Mineralogy - Kelvin, Michelle; Whiteman, Elizabeth; Leybourne, Matthew (Frontiers in Earth Science, 2022)
Monitoring emissions of particulate matter generated at mining operations is important to ensure the health and safety of workers and limit emissions entering the environment. Conventional methods of analyzing particulate matter, such as chemical assay, do not always provide enough detail to determine origin of emissions, the extent that they enter the environment, or to understand the toxicology associated with exposure. In this study, we have used a combination of quantitative mineralogy (QEMSCAN) and baseline monitoring to characterize the types of nickel present in airborne dust at a nickel smelter. The objective of the analysis was to determine which activities produce dust. QEMSCAN analysis provided detailed inspection of individual particulates and statistically robust information related to characterizing dust within the inhalable size ranges. Strategic sampling allowed investigation of dust generation surrounding key locations at the smelter.